2019
DOI: 10.1080/09537104.2019.1624708
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tissue factor in platelets: why is it so troublesome?

Abstract: Detection of tissue factor in platelets: why is it so troublesome?Tissue factor (TF) is the most important trigger for the extrinsic coagulation pathway. TF, earlier denoted as thromboplastin, has always been a mystery since its discovery due to its abundant presence in most human tissues but not blood. The latter has been extensively studied in a vast quest for possible sources of blood-borne TF yielding many conflicting findings and confusing conclusions regarding the presence of TF mRNA, protein or function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Here, we describe that TF-negative platelet-derived EVs enhance FVIIa-dependent FXa production on undamaged fibroblasts despite having virtual no ability to support FXa generation alone. The platelet-EVs and liposomes used in our experiments did not support TF activity [43] but had high levels of externalised PS and PE. The enhanced fibroblast-dependent FX activation was inhibited by annexin V, demonstrating that PS or PE were important for the effect but in this case the PS/PE were from a source that was exogenous to the undamaged fibroblasts.…”
Section: Plos Onementioning
confidence: 85%
“…Here, we describe that TF-negative platelet-derived EVs enhance FVIIa-dependent FXa production on undamaged fibroblasts despite having virtual no ability to support FXa generation alone. The platelet-EVs and liposomes used in our experiments did not support TF activity [43] but had high levels of externalised PS and PE. The enhanced fibroblast-dependent FX activation was inhibited by annexin V, demonstrating that PS or PE were important for the effect but in this case the PS/PE were from a source that was exogenous to the undamaged fibroblasts.…”
Section: Plos Onementioning
confidence: 85%
“…However, this assumption is the subject of a controversial discussion, as other, flow cytometric based, investigations indicated that no TF would be expressed on activated platelets ( 117 ). Only recently has the debate whether platelets can release TF by themselves been portrayed elsewhere in detail ( 118 , 119 ). Regardless of this debate, platelet CD40L expression has been reported to induce monocyte expression of tissue factor, which in turn activates the extrinsic coagulation cascade ( 120 ); thus, emphasizing the intimate interaction between platelets, immune cells and the plasmatic coagulation system.…”
Section: Platelet Receptors and Interactions In The Context Of Thrombmentioning
confidence: 99%
“…64 Both the antigen and the procoagulant activity of TF have been detected on platelets, 8,65 although Østerud and Olsen and Bouchard et al contradicted these findings, [66][67][68][69] likely due to methodological differences. 70,71 Platelet granular contents have been shown to influence TG. An illustrating example was found in FV-deficient patients who have no detectable plasma FV and PPP-TG, in which the absence of life-threatening bleedings could be explained by FV contribution from platelets leading to sufficient PRP-TG.…”
Section: Influence Of Platelet Granule Secretion On Prp-tgmentioning
confidence: 99%